Effects of lysine and threonine on milk yield, amino acid metabolism, and fecal microbiota of Yili lactating mares - Lin, Jianwei; Jing, Hongxin; Wang, Jianwen; Lucien-Cabaraux, Jean-Francois; Yang, Kailun; Liu, Wujun; Li, Xiaobin (Frontiers in Veterinary Science, 2024)
This study investigated the effects of lysine and threonine supplementation on 24 healthy Yili mares, mares at day 30 of lactation, over a 120day period. The mares were divided into control and three experimental groups (six mares each) under pure grazing conditions. The control group received no amino acid supplementation, while experimental groups received varying daily doses of lysine † These authors contributed equally to this article. and threonine: Group I (40g lysine + 20g threonine), Group II (60g lysine + 40g threonine), and Group III (80g lysine + 60g threonine). Supplementation in Group II notably increased milk yield, while Groups I and II showed higher milk fat percentages, and all experimental groups exhibited improved milk protein percentages.Additionally, blood levels of total protein, albumin, triglycerides, and glucose were reduced. Detailed analyses from Group II at peak lactation (day 60) included targeted metabolomics and microbial sequencing of milk, blood, and fecal samples. Amino acid metabolomics assessed amino acid content in mare milk and serum, while 16S rRNA gene sequencing evaluated rectal microbial composition. The results indicated that lysine and threonine supplementation significantly increased levels of threonine and creatine in the blood, and lysine, threonine, glutamine, and alanine in mare milk.Microbial analysis revealed a higher prevalence of certain bacterial families and genera, including Prevotellaceae, p_251_o5, and Rikenellaceae at the family level, and unclassified_p_251_o5, Prevotellaceae_UCG_001 and Rikenellaceae_RC9_gut_group at the genus level. Multi-omics analysis showed positive correlations between specific fecal genera and amino acids in mare milk. For instance, Prevotellaceae_UCG_003, unclassified Bacteroidetes_BS11_gut_group, and Corynebacterium were positively correlated with lysine, while unclassified Prevotellaceae was positively correlated with alanine and threonine, and Unclassified_Bacteroidales_BS11_gut_group was positively correlated with glutamine. In summary, lysine and threonine supplementation in grazing lactating mares enhanced milk production and improved milk protein and fat quality. It is recommended that herders, veterinarians, and technicians consider amino acid content in the diet of lactating mares. The optimal supplementation levels under grazing conditions for Yili horses were determined to be 60g lysine and 40g threonine per day.